2016
DOI: 10.1007/s11103-016-0568-2
|View full text |Cite
|
Sign up to set email alerts
|

The protein phosphatase 2C clade A protein OsPP2C51 positively regulates seed germination by directly inactivating OsbZIP10

Abstract: Protein phosphatase 2C clade A members are major signaling components in the ABA-dependent signaling cascade that regulates seed germination. To elucidate the role of PP2CA genes in germination of rice seed, we selected OsPP2C51, which shows highly specific expression in the embryo compared with other protein phosphatases based on microarray data. GUS histochemical assay confirmed that OsPP2C51 is expressed in the seed embryo and that this expression pattern is unique compared with those of other OsPP2CA genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…Note: GS: germination stage; SSI: the sampling point I at seedling stage; SSII: the sampling point II at seedling stage; SSIII: the sampling point III at seedling stage to be involved in abscisic acid signal transduction in higher plants (Sheen, 1998). Three PP2Cs (AtPP2CG1, AtPP2CA, and OsPP2C51) were found to enhance salinity tolerance in an abscisic acid-dependent mannerin Arabidopsis and promoted seed germination in rice (Liu et al, 2012;Cui et al, 2013;Bhatnagar et al, 2017). We detected a high level of ABA in the leaves and roots of CMG under salt stress in the seedling stage and the expression of OsPP2C8 was significantly up-regulated at the three sampling points in the seedling stage.…”
Section: Mapping Candidate Regions For Salinity Tolerance In Cmgmentioning
confidence: 81%
“…Note: GS: germination stage; SSI: the sampling point I at seedling stage; SSII: the sampling point II at seedling stage; SSIII: the sampling point III at seedling stage to be involved in abscisic acid signal transduction in higher plants (Sheen, 1998). Three PP2Cs (AtPP2CG1, AtPP2CA, and OsPP2C51) were found to enhance salinity tolerance in an abscisic acid-dependent mannerin Arabidopsis and promoted seed germination in rice (Liu et al, 2012;Cui et al, 2013;Bhatnagar et al, 2017). We detected a high level of ABA in the leaves and roots of CMG under salt stress in the seedling stage and the expression of OsPP2C8 was significantly up-regulated at the three sampling points in the seedling stage.…”
Section: Mapping Candidate Regions For Salinity Tolerance In Cmgmentioning
confidence: 81%
“…In Arabidopsis, a PP2C protein, HONSU, which acts as a negative regulator of ABA signaling, modulates the expression of GA metabolism and signaling genes and thereby enhance the transition of seeds from dormant to germinating state ( Kim et al, 2013 ). In cereals such as rice, PP2C protein represses OsbZIP10 ( ABI5 homolog of rice) via dephosphorylation and thereby promote seed germination ( Bhatnagar et al, 2017 ). Consistently, overexpression of OsPP2C51 leads to increased expression of α -amylase and activity of the corresponding enzyme.…”
Section: Abscisic Acid/gibberellin Balance Controls Seed Dormancy Andmentioning
confidence: 99%
“…A n o t h e r l o c u s e n c o d e s t o LOC_Os03g29810, which controls several functions in the synthesis of plastidic proteins in the chloroplast and regulates the photosynthesis mechanism (Dong et al 2013;van Campen et al 2016). Two genes on chromosome 6 (LOC_Os06g17220 and LOC_Os06g48300) are responsible for sucrose synthetic activity and tolerance of anoxia condition during germination (Lasanthi-Kudahettige et al 2007) and regulate the major ABAdependent signaling component, which is involved in a high rate of germination (Bhatnagar et al 2017). Singh et al (2015) revealed that the OsPP108 gene of the PP2C family significantly enhanced tolerance of drought, cold, and salinity during seed germination.…”
Section: Putative Candidate Genes In Co-localized M-qtlsmentioning
confidence: 99%